Mr. Monk and the two assistants - Goldberg, Lee, 1962- (Monk series (New York, N.Y.), 2007)
Now that her ne'er-do-well husband has been arrested for murder, Monk's former assistant, Sharona, is ready to reclaim her place in Monk's extremely well-ordered life. But his current assistant, Natalie, is not pleased with this turn of events. While Monk tries to maintain a delicate balance between the two women, he discovers a few snags in the case against Sharona's husband. And with other murders to investigate, Monk realizes he may be up against a killer who not only understands him, but is one step ahead.